DIAGNOSTIC CRITERIA AND ATTENTIVE REVIEWS IN THE TREATMENT OF CARDIAC X SYNDROME ANICIZED PATIENTS - Umarhanov N.М,; Tashtemirova I.M, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
To assess coronary hemodynamic status in patients with cardiological x-syndrome. Those with cardiological x-syndrome had a much lower coronary reserve. Less myocardial vascularization, more severe diffuse cardiosclerosis that reduced the capillaries' dilatory reserve, and injury localization at the prearteriole, arteriole, and capillary levels (i.e., in the region of the coronary vascular bed most responsible for dilator reserve) were the factors that led to low coronary flow reserve values.